Situation Analysis and Needs Assessment Report for Pailom Village, Savannakhet Province, Lao PDR - Bui Tan Yen; Jerome Villanueva; Keophoxay, Anousith; Grant, Angela; Soytavanh, Mienmany; Phonevisay Silivong; Khodyhotha, Khamphamy; Ferrer, Alice J.; Sebastian, Leocadio S. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2015)
The Situation Analysis and Needs Assessment is part of the baseline study of CCAFS climate-smart villages in Southeast Asia. Focus group discussions, key informant interviews, and collection of secondary data were conducted from the village to provincial levels. The Pailom village, one of CCAFS benchmark sites, is located in Champhone district, Savannakhet Province, Laos. Savannakhet province is lowland at the western part and the upland at the eastern part. The province, including Pailom village, frequently experiences drought and crop damage from pests and diseases. Rice production is the main source of people’s livelihood. Due to lack of irrigation and low fertile soil, rice yield is low, ranging from 1.5 to 4.5 tons per hectare. The increasing population growth and negative impacts of climate change contribute to the yearly food shortage in the area. The number of migrant workers from the rural area of the province to the cities and neighboring countries, especially Thailand is increasing. There are not many organizations operating in Pailom village and it is equally uncommon to find organizations working on food security and food crisis issues. Information networking for agricultural activities is mainly established between farmers. There is poor dissemination of agricultural information or technical support from agricultural extension workers and responsible agencies. The identified priorities of farmers in Pailom village include strengthening and promoting agricultural research extension to gather information on fertilizer management, sustainable agricultural production techniques, pest and disease management, and adoption of drought and salinity resistant crop varieties and appropriate husbandry techniques.